2001
DOI: 10.1080/1120009x.2001.11782327
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance in Developing Countries

Abstract: During the past decade there have been major changes in the susceptibility of bacteria that cause various infections. Resistance to anti-infective agents, including antibiotics, is worldwide, both in developed and developing countries. Almost all bacterial species can develop resistance to anti-infective agents and resistance can readily be transferred among bacteria by transmissible elements (plasmids). Measures to prevent the emergence of resistance must be implemented urgently. A multiplicity of factors dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Information on infection epidemiology and antimicrobial resistance patterns is a critical means to help physicians empirically treat life-threatening infectious illnesses. Several studies reported a correlation between increasing the AMR rate and increasing antibiotic use [4,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Information on infection epidemiology and antimicrobial resistance patterns is a critical means to help physicians empirically treat life-threatening infectious illnesses. Several studies reported a correlation between increasing the AMR rate and increasing antibiotic use [4,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that low-income countries like Bangladesh are more affected by AMR because of the widespread misuse of antibiotics, non-human antibiotic use, poor quality of drugs, inadequate surveillance and factors associated with individual and national poverty indicators like poor healthcare standards, malnutrition, chronic and repeated infections, unaffordability of more effective and costly drugs [9, 10]. Research regarding antibiotic resistance epidemiology may ultimately guide to interventions for AMR.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization, in its late report released in April 2014, revealed that antibiotic resistance is a serious and growing global problem [ 6 ]. Several studies reported the relationship between antibiotic use and the development of resistance [ 7 9 ]. Countries consuming the highest amounts of antibiotics have the highest rates of resistance [ 10 ].…”
Section: Introductionmentioning
confidence: 99%